Analisis Biaya Sosial Kaitannya Dengan Penghasilan Kena Pajak - Poere, Daniel De; Sukadi, Johanes; Sabri, Rizki Amelia (Institut Bisnis dan Informatika Kesatuan, 2015)
The amount of social costs may affect the tax burden of a company. Thus, social expenses spent by the company basically determined based on annual income. However, not all social expenses deduct the gross income, some are included in social expenses but not reducing the tax obligations. This research is aimed at evaluating the extent of a company's awareness towards neighborhood and surrounding society, and how it is affecting the company 's profit to pay its tax. Kata kunci: Company Social Responsibility, Tax Obligations